2007
DOI: 10.1021/je700307r
|View full text |Cite
|
Sign up to set email alerts
|

Experimental PT−ρ Measurements of Supercritical Mixtures of Carbon Dioxide, Carbon Monoxide, and Hydrogen and Semiquantitative Estimation of Their Solvent Power Using the Solubility Parameter Concept

Abstract: The P-T-F behavior of the CO 2 -CO-H 2 system was studied in the supercritical region under operative conditions close to those adopted to perform hydrogenation and hydroformylation reactions in dense CO 2 , thus providing new interesting information on this fluid mixture. Experiments were performed in a fixed volume reactor in the temperature range from 298 K to 343 K changing the density and the composition of the fluid phase. The onecomponent (Hildebrand) solubility parameter of the mixture was estimated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 15 publications
2
19
0
Order By: Relevance
“…The density data of Cipollina et al . 15 are at pressures too high to be able to extract virial coefficients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The density data of Cipollina et al . 15 are at pressures too high to be able to extract virial coefficients.…”
Section: Resultsmentioning
confidence: 99%
“…The few available vapor-liquid 46 and vapor-solid 7,8 equilibrium data are at cryogenic temperatures far from the conditions of most industrial interest. The available gas-phase data 9–15 will be discussed in Section IV C.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, much attention has been given to studies of the thermodynamic properties, such as vapour-liquid equilibrium (VLE) and density of CO2 mixtures with impurities. A number of research groups have studied some of these key binaries, such as CO2/N2 (Fandino et al, 2015;Mantovani et al, 2012;Tenorio et al, 2015;Westman et al, 2016b), CO2/Ar (Coquelet et al, 2008;Köpke and Eggers, 2007;Mantovani et al, 2012;Yang et al, 2015a), CO2/H2 (Cipollina et al, 2007;Fandino et al, 2015;Sanchez-Vicente et al, 2013;Tenorio et al, 2015), CO2/O2 (Mantovani et al, 2012;Westman et al, 2016a), CO2/SO2 (Coquelet et al, 2014;Köpke and Eggers, 2007), CO2/CO (Cipollina et al, 2007), CO2/H2S (Chapoy et al, 2013a) and CO2/H2O (Hou et al, 2013;Valtz et al, 2004), which either focused on the binaries with an insufficient amount of data under the conditions relevant to CCS or aimed at reducing experimental uncertainties. A comprehensive data survey of the available thermodynamic properties of binary systems with CO2 can be found in the monograph by Kunz et al (2007) and in the recent reviews by Munkejord et al (2016) and Li.…”
Section: Introductionmentioning
confidence: 99%
“…A single value of the solubility parameter of scCO 2 was reported by Wai and Wang 33 without disclosing its source: δ H /MPa 1/2 = 13.5 at T = 333.15 K and P = 22.7 MPa. Cipollina et al 34 also specified this temperature, T = 333 K, but reported only the range of pressures 7 ≤ P/ MPa ≤ 40 at which 2.7 ≤ δ H /MPa 1/2 ≤ 12.6, values that are rather lower than those given by other authors. The most recent and definite equation of state of Span and Wagner 35 for carbon dioxide yielded numerical data of the specific internal energies and densities for supercritical conditions.…”
Section: Solubility Parameters Of Scco2mentioning
confidence: 92%